Magnetic refrigeration alloy with triangular anti-filing structure as well as preparation method and application of magnetic refrigeration alloy

By developing a magnetic refrigeration alloy ErPd2Sb with a triangular blocking structure, combined with arc smelting method and quasi-adiabatic demagnetization refrigeration equipment, the problems of thermal conductivity and magnetic order temperature of existing ultra-low temperature magnetic refrigeration materials have been solved, and efficient magnetothermal performance has been achieved and simplified preparation process, suitable for low-temperature magnetic refrigeration applications.

CN119121027APending Publication Date: 2024-12-13HANGZHOU DIANZI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411261574.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing ultra-low temperature magnetic refrigeration materials have shortcomings in thermal conductivity and magnetic order temperature, and it is difficult to meet high magneto-thermal effects and low thermal conductivity at the same time, which limits the development of magnetic refrigeration technology, especially in space environments.

Method used

A magnetic refrigeration alloy ErPd2Sb with a triangular blocking structure was developed, which was prepared by arc smelting method and combined with quasi-adiabatic demagnetization refrigeration equipment to achieve efficient magnetothermal performance at low temperatures.

Benefits of technology

ErPd2Sb material exhibits a large magneto-thermal effect near the phase transition temperature of 0.56K, with a maximum magnetic entropy change of 21.6J·kg-1·K-1, and can operate at the lowest temperature of 0.255K, with excellent thermal conductivity and simplification. The preparation process is suitable for large-scale industrial production and low-temperature magnetic refrigeration applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121027A_ABST
    Figure CN119121027A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic refrigeration alloy with a triangular anti-contusion structure and a preparation method and application of the magnetic refrigeration alloy, the chemical formula of the magnetic refrigeration alloy is ErPd2Sb, the phase change temperature is 0.56 K, and when the magnetic field change is 7T, the maximum magnetic entropy of the magnetic refrigeration alloy is changed to 21.6 J.kg <-1 >. K <-1 > (1.4 K); when quasi-adiabatic demagnetization refrigeration equipment is used for testing, when the initial magnetic field is 6T and the initial temperature is 2K, the lowest temperature that ErPd2Sb can reach is 0.255 K. The preparation method comprises the following steps: 1) weighing raw materials Er, Pd and Sb, putting the raw materials into a crucible of a high-vacuum arc furnace, filling protective gas, and smelting; and (2) after smelting is completed, a sample is completely wrapped with a tantalum sheet and sealed in a quartz tube to be annealed, and the low-temperature magnetic refrigeration alloy is prepared. The method does not need to use acid or alkali or other substances which cause serious pollution to the environment, has the remarkable advantages of being green and environmentally friendly, and is simple in preparation process and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic refrigeration materials, and specifically comprises a magnetic refrigeration alloy with a triangular frustration structure, and a preparation method and application thereof. Background Art

[0002] Ultra-low temperature (<1K) has become a necessary condition for the development of many cutting-edge science and technology. At present, the main ways to obtain ultra-low temperature include helium-3 adsorption refrigeration, helium-3-helium-4 dilution refrigeration and adiabatic demagnetization refrigeration (ADR). Among them, ADR has become the most widely used ultra-low temperature refrigeration technology in space environment due to its advantages of high efficiency, low energy consumption, independence from gravity and helium-3.

[0003] ADR uses the magnetocaloric effect of magnetic materials to achieve cooling, that is, the magnetocaloric properties of magnetic refrigeration materials play a key role in ADR. At present, the exploration of ultra-low temperature magnetic refrigeration materials is mainly focused on paramagnetic salts with weak magnetic interactions. Although paramagnetic salt materials are relatively easy to obtain larger magnetocaloric properties, due to the existence of magnetic interactions, there is always long-range order in the system; on the other hand, the mainstream magnetic refrigeration materials are oxides, and their low thermal conductivity is not conducive to heat exchange in the magnetic refrigeration process. Therefore, it is crucial to find a magnetic refrigeration material that simultaneously satisfies the requirements of large magnetocaloric effect, low order temperature and excellent thermal conductivity.

[0004] Fortunately, researchers have discovered a magnetic material system with a triangular lattice, namely the frustrated magnetic system. Compared with traditional paramagnetic salts, the localized magnetic moments in frustrated magnets cannot be satisfied simultaneously due to competing magnetic interactions, resulting in a large number of degenerate states in the ground state of the system; at the same time, the spins in frustrated magnets are highly correlated, and even at absolute zero, there are still strong fluctuations, resulting in the absence of long-range order at extremely low temperatures. Therefore, frustrated magnets have the potential to simultaneously satisfy large ground state entropy and low magnetic order temperature. On the other hand, since the alloy system is mainly electronically conductive, its thermal conductivity is significantly better than that of oxide materials, which is more conducive to obtaining high heat exchange efficiency. Therefore, the development of a frustrated magnetic alloy that is simple to prepare and has a large magnetocaloric effect is of great significance to the development of compact, miniaturized and integrated commercial magnetic refrigeration devices. Summary of the invention

[0005] Purpose of the invention: In view of the above problems existing in the prior art, the first purpose of the present invention is to provide a magnetic refrigeration alloy having a triangular frustration structure. The second purpose of the present invention is to provide a method for preparing a magnetic refrigeration alloy having a triangular frustration structure. The third purpose of the present invention is to provide an application of the magnetic refrigeration alloy having a triangular frustration structure as described above in low-temperature magnetic refrigeration.

[0006] The technical solution adopted by the present invention is: a magnetic refrigeration alloy with a triangular frustrated structure, the chemical formula of the magnetic refrigeration alloy is ErPd2Sb, and its phase transition temperature is 0.56K. The low-temperature magnetic refrigeration alloy of the present invention exhibits a large magnetocaloric effect near the phase transition temperature.

[0007] When the magnetic field changes to 7T, the maximum magnetic entropy change of the magnetic refrigeration alloy is 21.6J·kg -1 ·K -1 (1.4K).

[0008] The magnetic refrigeration alloy is tested using a quasi-adiabatic demagnetization refrigeration device. When the initial magnetic field is 6T and the initial temperature is 2K, the lowest temperature that can be reached is 0.255K.

[0009] The magnetic refrigeration alloy having a triangular frustration structure comprises at least one of the following (1) and (2):

[0010] (1) The magnetic refrigeration alloy is composed of a single phase, belongs to the cubic crystal system, has a space group of Fm3m, and a unit cell parameter of

[0011] (2) The Er in the magnetic refrigeration alloy forms an equilateral triangle in the structure, and the side length is

[0012] The present invention also provides a method for preparing a magnetic refrigeration alloy having a triangular frustration structure, comprising the following steps:

[0013] Step 1: Weigh corresponding amounts of raw materials Er, Pd and Sb, put them into a crucible of a high vacuum arc furnace, fill it with protective gas, and perform smelting;

[0014] Step 2: After smelting, the sample is completely wrapped with a tantalum sheet and sealed in a quartz tube for annealing to obtain the low-temperature magnetic refrigeration alloy.

[0015] In the present invention, through a simple melting furnace and annealing, technicians successfully synthesized the ErPd2Sb low-temperature magnetic refrigeration alloy. The synthesis method has a simple process, a short synthesis cycle, and lower requirements for the reaction environment, and is suitable for large-scale industrial production.

[0016] Preferably, in step 1, when the molar ratio of Er, Pd and Sb is 1.01-1.05:2-2.02:1, the impurity ratio of the target product can be reduced. It can be understood that the molar ratio of Er, Pd and Sb includes but is not limited to 1.01:2:1, 1.02:2:1, 1.03:2:1, 1.04:2:1, 1.05:2:1, 1:2.01:1, 1:2.02:1.

[0017] Preferably, in step 1, the protective gas is argon.

[0018] Preferably, during smelting in step 1, the pressure parameter is 0.5 Pa and the current parameter is 150 A.

[0019] Preferably, in step 2, the annealing temperature is 1123-1173K, and the annealing time is 3-5 weeks.

[0020] The present invention also seeks to protect the application of the low-temperature magnetic refrigeration alloy in a low-temperature magnetic refrigeration system.

[0021] When the magnetic refrigeration alloy with a triangular frustration structure is applied to low-temperature magnetic refrigeration, the prepared material is first placed in an ambient temperature range of 0.4-1.5K, and the ambient magnetic field strength is set to decrease from 7T to 0T, so that the magnetic refrigeration material has a maximum magnetic entropy change of 21.6J kg -1 K -1 ; Then place the prepared material in an initial ambient temperature of 2K, and set the ambient magnetic field strength to decrease from 6T to 0T, so that the magnetic refrigeration material has the lowest cooling temperature of 0.255K.

[0022] Beneficial effects:

[0023] The phase transition temperature of the magnetic refrigeration alloy with a triangular frustration structure prepared by the present invention is 0.56K, and the lowest temperature of 0.255K can be reached by quasi-adiabatic demagnetization refrigeration. It is expected to be used on a large scale as a magnetic refrigeration material in the ultra-low temperature zone to replace liquid helium refrigeration.

[0024] The present invention selects ErPd2Sb, which is an alloy. Compared with oxide magnetic refrigeration materials, it has better thermal conductivity and greater magnetocaloric performance: the maximum magnetic entropy change reaches 21.6 J·kg at 1.4K and a magnetic field change of 7T. -1 ·K -1 , which has broad application prospects.

[0025] The preparation method of the low-temperature magnetic refrigeration alloy provided by the present invention is an arc melting method, which has a simple preparation process, a short preparation cycle, low energy consumption, and is suitable for large-scale industrial production. The application of the low-temperature magnetic refrigeration alloy in the field of magnetic refrigeration technology is not only conducive to the development of my country's low-temperature physics, space exploration, aerospace and other technologies, but also helps to promote the high-value utilization of my country's rare earth resources and enhance the competitiveness and technical level of my country's rare earth industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the crystal structure diagram of ErPd2Sb alloy;

[0027] Figure 2This is the XRD refinement diagram of the ErPd2Sb alloy prepared in Example 1;

[0028] Figure 3 The temperature-dependent magnetic susceptibility curve and Curie-Weiss fitting curve of the ErPd2Sb alloy prepared in Example 1;

[0029] Figure 4 The temperature-variable field-variable magnetization intensity diagram of the ErPd2Sb alloy prepared in Example 1;

[0030] Figure 5 Magnetic entropy change diagram of the ErPd2Sb alloy prepared in Example 1;

[0031] Figure 6 This is the quasi-adiabatic demagnetization curve of the ErPd2Sb alloy prepared in Example 1. DETAILED DESCRIPTION

[0032] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. In addition, unless otherwise specified, the raw materials used in the present invention can be obtained by commercial purchase, and any range recorded in the present invention includes any end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0033] Example 1

[0034] The ErPd2Sb alloy was prepared and tested by arc melting method, including the following steps:

[0035] Step 1: According to the molar ratio of Er, Pd and Sb of 1.01:2:1, weigh the corresponding amount of Er, Pd and Sb, put Sb into the crucible of the arc furnace first, then cover the top of Sb with Er and Pd, then purge the arc furnace with argon twice to ensure an oxygen-free environment, fill with argon to a pressure of 0.5Pa, and then use an arc to melt the sample at a current of 150A.

[0036] Step 2: The prepared metal ingot is wrapped with a tantalum sheet and sealed in a quartz tube filled with argon, and kept in a muffle furnace at 1153K for 4 weeks to prepare an ErPd2Sb alloy.

[0037] Step 3: The ErPd2Sb alloy prepared in this embodiment is characterized in structure: The crystal structure of the ErPd2Sb alloy is shown in FIG. Figure 1 As shown, ErPd2Sb is a cubic lattice. Figure 1 (a) in the unit cell; 3+ The ions form a An equilateral triangle, Figure 1(b) in the figure indicates its geometrically frustrated nature. The existence of geometric frustration is conducive to achieving a low magnetic ordering temperature.

[0038] The ErPd2Sb alloy obtained in this example was characterized by XRD. Figure 2 As shown. It can be found that the measured sample is basically consistent with the standard PDF card, indicating that it is a pure phase. The unit cell parameters obtained by refinement are

[0039] Step 4: Conduct magnetic testing on the ErPd2Sb alloy prepared in this example. Use a superconducting quantum interference device (SQUID) and a modified comprehensive physical property measurement system (PPMS) to study its magnetocaloric effect:

[0040] The temperature-dependent magnetic susceptibility curve of ErPd2Sb alloy was measured under the conditions of magnetic field of 0.01T and temperature of 1.8 to 100K, as shown in Figure 3 As shown in (a). It can be found that no magnetic phase transition is observed in the test temperature range, indicating that ErPd2Sb is paramagnetic above 1.8K. According to the Curie-Weiss theorem, the paramagnetic Curie temperature θ is obtained by linearly fitting the inverse curve of the variable temperature magnetic susceptibility. P =-6.23K. Negative θ P This indicates that ErPd2Sb alloy has weak antiferromagnetic coupling and is suitable for use as a magnetic refrigeration material. In order to further determine the phase transition temperature of ErPd2Sb, its temperature-dependent magnetic susceptibility curve at 0.4-1.5K was tested, as shown in Figure 2. Figure 3 As shown in (b). The test results prove the antiferromagnetic ground state of ErPd2Sb, and the phase transition temperature is 0.56K. In addition, the calculated frustration parameter |θ P / T N | is 11. The large frustration parameter indicates that ErPd2Sb has strong frustration properties.

[0041] The temperature-variable field magnetization intensity curves of ErPd2Sb alloy measured under the conditions of temperature range of 0.4-1.5K and magnetic field range of 0-7T are shown in Figure 4 As shown in Figure 2, the magnetization intensity of the ErPd2Sb alloy gradually increases with the increase of the magnetic field, and reaches a maximum value of 75.6emu / g at a temperature of 0.4K and a magnetic field of 7T. Figure 4 The inset is the intersection of the magnetization curves at 0.4K and 0.5K. It can be found that at a smaller critical field (0.165T), the two magnetization curves intersect, indicating that Er in the ErPd2Sb alloy 3+ The magnetic interactions between ions are weak.

[0042] The magnetic entropy change of ErPd2Sb alloy was calculated according to Maxwell's relationship. The results are as follows: Figure 5 As shown in the figure, the maximum magnetic entropy change of the material at 1.4K and a magnetic field change of 7T is 21.6J kg -1 K -1 .

[0043] The magnetocaloric properties of ErPd2Sb alloy were tested using a quasi-adiabatic demagnetization refrigeration device. The results are as follows: Figure 6 It can be found that when the initial magnetic field is 6T and the initial temperature is 2K, the lowest temperature that ErPd2Sb can reach is 0.255K.

[0044] Example 2

[0045] The ErPd2Sb alloy was prepared and tested by arc melting method, including the following steps:

[0046] Step 1: According to the molar ratio of Er, Pd and Sb of 1.03:2:1, weigh the corresponding amount of Er, Pd and Sb, put Sb into the crucible of the arc furnace first, then cover the top of Sb with Er and Pd, then purge the arc furnace with argon twice to ensure an oxygen-free environment, fill with argon to a pressure of 0.5Pa, and then use an arc to melt the sample at a current of 150A.

[0047] Step 2: The prepared metal ingot is wrapped with a tantalum sheet and sealed in a quartz tube filled with argon, and kept in a muffle furnace at 1153K for 4 weeks to prepare an ErPd2Sb alloy.

[0048] Step 3: XRD was used to characterize the ErPd2Sb alloy obtained in this example, and the results were basically consistent with the theoretical spectrum.

[0049] Example 3

[0050] The ErPd2Sb alloy was prepared and tested by arc melting method, including the following steps:

[0051] Step 1: According to the molar ratio of Er, Pd and Sb of 1.01:2.01:1, weigh the corresponding amount of Er, Pd and Sb, put Sb into the crucible of the arc furnace first, then cover the top of Sb with Er and Pd, then purge the arc furnace with argon twice to ensure an oxygen-free environment, fill with argon to a pressure of 0.5Pa, and then use an arc to melt the sample at a current of 150A.

[0052] Step 2: The prepared metal ingot is wrapped with a tantalum sheet and sealed in a quartz tube filled with argon, and kept in a muffle furnace at 1153K for 4 weeks to prepare an ErPd2Sb alloy.

[0053] Step 3: XRD was used to characterize the ErPd2Sb alloy obtained in this example, and the results were basically consistent with the theoretical spectrum.

[0054] Example 4

[0055] The ErPd2Sb alloy was prepared and tested by arc melting method, including the following steps:

[0056] Step 1: According to the molar ratio of Er, Pd and Sb of 1.01:2:1, weigh the corresponding amount of Er, Pd and Sb, put Sb into the crucible of the arc furnace first, then cover the top of Sb with Er and Pd, then purge the arc furnace with argon twice to ensure an oxygen-free environment, fill with argon to a pressure of 0.5Pa, and then use an arc to melt the sample at a current of 150A.

[0057] Step 2: The prepared metal ingot is wrapped with a tantalum sheet and sealed in a quartz tube filled with argon, and kept in a muffle furnace at 1123K for 4 weeks to prepare an ErPd2Sb alloy.

[0058] Step 3: XRD was used to characterize the ErPd2Sb alloy obtained in this example, and the results were basically consistent with the theoretical spectrum.

[0059] Example 5

[0060] The ErPd2Sb alloy was prepared and tested by arc melting method, including the following steps:

[0061] Step 1: According to the molar ratio of Er, Pd and Sb of 1.01:2:1, weigh the corresponding amount of Er, Pd and Sb, put Sb into the crucible of the arc furnace first, then cover the top of Sb with Er and Pd, then purge the arc furnace with argon twice to ensure an oxygen-free environment, fill with argon to a pressure of 0.5Pa, and then use an arc to melt the sample at a current of 150A.

[0062] Step 2: The prepared metal ingot is wrapped with a tantalum sheet and sealed in a quartz tube filled with argon, and kept in a muffle furnace at 1153K for 5 weeks to prepare an ErPd2Sb alloy.

[0063] Step 3: XRD was used to characterize the ErPd2Sb alloy obtained in this example, and the results were basically consistent with the theoretical spectrum.

[0064] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A magnetic refrigeration alloy having a triangular frustration structure, characterized in that: The chemical formula of the magnetic refrigeration alloy is ErPd2Sb, its phase transition temperature is 0.56K, and its maximum magnetic entropy change is 21.6J·kg when the magnetic field changes to 7T. -1 ·K -1 ; Using quasi-adiabatic demagnetization refrigeration equipment to test, when the initial magnetic field is 6T and the initial temperature is 2K, the lowest temperature that ErPd2Sb can reach is 0.255K; The magnetic refrigeration alloy having a triangular frustration structure comprises at least one of the following (1) and (2): (1) The magnetic refrigeration alloy is composed of a single phase, belongs to the cubic crystal system, has a space group of Fm3m, and a unit cell parameter of (2) The Er in the magnetic refrigeration alloy forms an equilateral triangle in the structure, and the side length is 2. The method for preparing a magnetic refrigeration alloy having a triangular frustration structure according to claim 1, characterized in that: The following steps are involved: Step 1: weigh raw materials Er, Pd and Sb, put them into a crucible of a high vacuum arc furnace, fill it with protective gas, and smelt them; Step 2: After smelting, the sample is completely wrapped with a tantalum sheet and sealed in a quartz tube for annealing to obtain the low-temperature magnetic refrigeration alloy.

3. The method for preparing a magnetic refrigeration alloy having a triangular frustration structure according to claim 2, characterized in that: In the step 1, the raw material contains Er, Pd and Sb in a molar ratio of 1.01-1.05:2-2.02:

1.

4. The method for preparing a magnetic refrigeration alloy having a triangular frustration structure according to claim 2, characterized in that: In the step 1, the protective gas is argon.

5. The method for preparing a magnetic refrigeration alloy having a triangular frustration structure according to claim 2, characterized in that: During the smelting process in step 1, the pressure is 0.5 Pa and the current is 150 A.

6. The method for preparing a magnetic refrigeration alloy having a triangular frustration structure according to claim 2, characterized in that: In the step 2, the annealing temperature is 1123-1173K, and the annealing time is 3-5 weeks.

7. The application of a magnetic refrigeration alloy having a triangular frustration structure according to claim 1, characterized in that: When the magnetic refrigeration alloy with a triangular frustration structure is applied to low-temperature magnetic refrigeration, the prepared material is first placed in an ambient temperature range of 0.4-1.5K, and the ambient magnetic field strength is set to decrease from 7T to 0T, so that the magnetic refrigeration material has a maximum magnetic entropy change of 21.6J·kg -1 ·K -1 ; Then place the prepared material in an initial ambient temperature of 2K, and set the ambient magnetic field strength to decrease from 6T to 0T, so that the magnetic refrigeration material has the lowest cooling temperature of 0.255K.

Citation Information

Patent Citations

  • Low-temperature magnetic refrigeration material and preparation method and application thereof

    CN117174418A

  • Magnetic refrigerant

    JP2017039993A

  • Coherent spin valve and related devices

    US20060183002A1